Fingerprinting the Fractional Order Phase Transitions in AdS Black Holes - Chabab, Mohamed; Iraoui, Samir (Frontiers in Physics, 2021)
In this paper, we have extended and deepened the study on fractional order phase transition (FPT) of a charged AdS black hole performed in Ma:2019hvr. We have carried out a detailed analysis of FPT for several AdS black hole prototypes: black hole surrounded by quintessence background, 5D Gauss-Bonnet, D dimensional RN-AdS BH, and lastly Kerr black holes. We have shown that the 4/3 order FPT at critical points obtained in Ma:2019hvr still holds for the first three black holes systems, while for Kerr black holes, the fractional order is rather 1/3. These results suggest two remarkable features: Firstly 4/3 order phase transition can be assumed for asymptotically AdS black holes spherical solutions, secondly the fractional order is not universal and can be affected by the geometric symmetry.